Occupational Stress among Librarian and Library Staff in Universitas Airlangga Indonesia - Ratih Damayanti; Fadilatus Sukma Ika Noviarmi; Erwin Dyah Nawawinetu; Maisyatus Suadaa Irfana (Universitas Airlangga, 2020)
Introduction: As the other worker, librarian could be got occupational stress because of their duties. However, the duties of librarians and library staff seem trivial and monotonous to the general public. Precisely because it looks trivial and monotonous, research needs to be done related to work stress experienced by librarians and library staff. Aim of this study were to assessed the work stress experienced by librarians and library staff also analyze work stress related factors among librarians and library staff. Methods: In this observational analytic research that has cross sectional designed, occupational stress level was measured by HSE questionnaire and role conflict, carrier development and responsibility to person in organization were calculated by questionnaire in Manpower Minister Decree number 5 2018. Results: Most of the librarian and library staff experienced moderate level of occupational stress. Analysis of chi-square results proved that role conflicts and carrier development significantly related to occupational stress that was experienced by librarian and library staff in Airlangga University. On the other hand, the other variables of socio-demographic and responsibility to person in organization have no significant relationship. Conclusion: Almost all levels of work stress on librarians and library staff are middle to high level with factors related to role conflict and career development.Keywords: Indonesia, librarian, occupational stress, university